2012
DOI: 10.1038/cddis.2012.169
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Uromodulin-like1 accelerates follicle depletion and subsequent ovarian degeneration

Abstract: Murine Uromodulin-like 1 (Umodl1) encodes Ca2+-dependent EGF-like membrane-bound proteins. This study presents its novel expression in the immune and female reproductive systems. Upon stimulation by CD3/CD28 antibodies, Umodl1 showed a prompt and robust response in the proliferating CD4+ T cells, suggesting its implication in immune defense against pathogens. In ovary, Umodl1 is regulated by gonadotropins. Mice carrying extra copies of functional Umodl1 were generated by BAC transgenesis. Defects in the female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Uromodulin-like 1 (UMODL1) helps regulate ovarian development in mice (Wang et al 2012). Regulatory factor X4 (RFX4) is highly expressed in the central nervous system in mice and may mediate ciliogenesis by modulating Sonic hedgehog (Shh) signaling during development (Ashique et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Uromodulin-like 1 (UMODL1) helps regulate ovarian development in mice (Wang et al 2012). Regulatory factor X4 (RFX4) is highly expressed in the central nervous system in mice and may mediate ciliogenesis by modulating Sonic hedgehog (Shh) signaling during development (Ashique et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study has now shown that the protein enhances proliferation of the cancer cells by regulating apoptosis (Chen et al, 2013). Furthermore, in rodents a uromodulin like-1 WFDSC domain-containing protein accelerates age-related ovarian degeneration (Wang et al, 2012). Given that carcinin is not only expressed in regenerating eyestalk, which is well supplied with neural fibres, but is also prominent in ovary and late-stage vitellogenic oocytes, it is not unreasonable to propose that it, and probably…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TNIK is proposed to be a biomarker of embryo viability in polycystic ovary syndrome (Huang et al, ), a prediction that matches the differential methylation state of TNIK in women with this disease (Wang et al, ). UMODL1 (SNV of 260,533,475 on chromosome 1) was reported to be expressed in both oocytes and the thymic medulla in mice. Interestingly, mice carrying an extra allele of Umodl1 have drastically reduced litter sizes and increased premature infertility at 6 months of age (Wang et al, ). These data suggest that disruptions to Uromodulin‐like 1 function may accelerate ovarian senescence and, in turn, implies a key role for this gene in fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…UMODL1 (SNV of 260,533,475 on chromosome 1) was reported to be expressed in both oocytes and the thymic medulla in mice. Interestingly, mice carrying an extra allele of Umodl1 have drastically reduced litter sizes and increased premature infertility at 6 months of age (Wang et al, ). These data suggest that disruptions to Uromodulin‐like 1 function may accelerate ovarian senescence and, in turn, implies a key role for this gene in fecundity.…”
Section: Discussionmentioning
confidence: 99%